Development of Practical Guidelines for Waste Processing Based on Liquid Organic Fertilizer Formulation Research for High School Biology Learning - Sholihah, Shafa Chamilatus; Al Habib, Ismul Mauludin; Sukamto, Dwi Sucianingtyas (Jurnal Paedagogy, 2025)
Abstract: This research aims to formulate a liquid organic fertilizer (LOF) based on banana corm, moringa leaves, and pineapple peel, providing a practical guide for organic waste processing in high school biology learning. The study used samples of organic waste (banana corm, moringa leaves, and pineapple peel) collected from Suci Village, Panti District, Jember Regency, which were then formulated into liquid fertilizer through a fermentation process lasting 14 days with the addition of bioactivators and other supporting materials. Data collection was conducted by observing the nutrient content of the LOF analyzed in the laboratory of Jember State University and validating the practical guide using validation sheets by three experts who assessed material, media, and language aspects on a Likert scale of 1–5. The validation data were analyzed descriptively and quantitatively by calculating the average percentage score to determine the product's validity level. Laboratory analysis showed that the resulting LOF contained Nitrogen (N) at 0.05%, Phosphorus (P) at 0.0032%, Potassium (K) at 0.005%, organic carbon at 0.62%, iron (Fe) at 0.00053%, and a pH of 3.4. The macro- and micronutrient content in this LOF is still below the minimum standards set by the Ministry of Agriculture; however, this formulation still provides an alternative for the value-added utilization of agricultural organic waste. The practical guide developed in this research has been validated by three expert validators with an average assessment percentage of 79.90%, indicating that this guide is valid for use in grade 10 high school biology learning on the topics of environmental change, waste, and recycling. The results show that this practical guide for making LOF is feasible to implement, contributing to organic waste management and contextual learning media that supports project-based environmental education. This study's outcomes have implications for developing innovative learning materials and promoting sustainable waste management practices in educational settings, ultimately enhancing environmental awareness and literacy among high school students.